A Low-Profile Ultra-Wideband Modified Planar Inverted-F Antenna - Chan Hwang See; Hraga, H. I.; Abd-Alhameed, R. A.; McEwan, N. J.; Noras, J. M.; Excell, P. S. (IEEE transactions on antennas and propagation, 2013)
A miniaturized modified planar inverted-F antenna (PIFA) is presented and experimentally studied. This antenna consists of a planar rectangular monopole top-loaded with a rectangular patch attached to two rectangular plates, one shorted to the ground and the other suspended, both placed at the optimum distance on each side of the planar monopole. The fabricated antenna prototype had a measured impedance bandwidth of 125%, covering 3 to 13 GHz for reflection coefficient better than -10 dB. The radiator size was 20×10×7.5 mm 3 , making it electrically small over most of the band and suitable for incorporation in mobile devices. The radiation patterns and gains of this antenna have been cross-validated numerically and experimentally and confirm that this antenna has adequate characteristics for short range ultra-wideband wireless applications.